THE INFLUENCE OF LEADERSHIP STYLE AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT HOTEL HARPER MAKASSAR - Nurindah Dian Lestari; Anwar Ramli, Muh. Ichwan Musa, Zainal Ruma, Uhud Darmawan Natsir (ADISAM Publisher, 2023)
This study aims to determine how the positive and significant influence of leadership style and work motivation on employee performance at Hotel Harper Makassar. In this study, the population of all employees at the Harper Hotel Makassar is 60 people and the sample is 40 people. Data collection was done by using a questionnaire method. The type of research used in this research is associative research. The data analysis technique used is data quality test, classical assumption test, multiple regression analysis, and the hypothesis is tested with multiple linear regression analysis. The results of the study after the data was processed with IBM statistics for product and service solution (SPSS) 25 it was found that Leadership Style and Work Motivation had a positive and significant effect on Employee Performance at Harper Hotel Makassar, it can be concluded that leadership style and work motivation have an influence on performance employees at Hotel Harper Makassar.